The iNOS Activity During an Immune Response Controls the CNS Pathology in Experimental Autoimmune Encephalomyelitis - Sonar, Sandip Ashok; Lal, Girdhari (Frontiers in Immunology, 2019)
Inducible nitric oxide synthase (iNOS) plays a critical role in the regulation of multiple sclerosis (MS) and experimental autoimmune encephalomyelitis (EAE). Previous studies have shown that iNOS plays pathogenic as well as regulatory roles in MS and EAE. However, how does iNOS alters the pathophysiology of the central nervous system (CNS) in neuronal autoimmunity is not clearly understood. In the present work, we show that treatment of mice with L-NAME, an iNOS inhibitor, during the antigen-priming phase primarily alters brain pathology, while in the subsequent effector phase of the immune response, the spinal cord is involved. Inhibition of iNOS during the priming phase of the immune response promotes the infiltration of pathogenic CD11b+F4/80-Gr-1+ cells, but there is low recruitment of regulatory CD11b+F4/80+ cells in the brain. Inhibition of iNOS during the effector phase shows similar pathogenic alterations in the spinal cord, instead of in the brain. Treatment of wild-type mice with L-NAME or mice having genetic deficiency of iNOS show lower MHC-II expression on the dendritic cells, but not on macrophages. Our data suggest that iNOS has a critical regulatory role during antigen-priming as well as in the effector phase of EAE, and inhibition iNOS at different stages of the immune response can differentially alter either the brain or spinal cord pathology. Understanding the cellular and molecular mechanisms through which iNOS functions could help to design better strategies for the clinical management of neuroinflammation and neuronal autoimmunity.